Analisis Historisitas Gerhana Di Desa Bissoloro Kec. Bungaya Kab. Gowa Perspektif Sains dan Ilmu Falak - SOMPA Sompa; Irfan Irfan; Cippah Cippah Chotban (HISABUNA: Jurnal Ilmu Falak, 2022)
Irfan, Nur Aisyah, Nila Sastrawati, Muh. Rasywan Syarif. Myths that develop in Indonesia society, especially in Bissoloro Village, Bungaya District, Gowa Regency, some people have their own beliefs in responding to the occurrence of the eclipse phenomenon by not doing activities outside the home, forbidding children to play outside the house, fearing they will get sick, and not being allowed to see the incident, the eclipse that occurs at night, it is believed that when the eclipse takes place, it is very suitable to uproot the lolo rupa plant to be used as a beauty potion for everyday use. This research is classified as a descriptive qualitative research field. The views of the people of Bissoloro Village in responding to the eclipse phenomenon still follow the beliefs of their ancestors. The development of science changes people’s assumptions, people who take education no longer think that eclipses are something to be afraid of, in fact the eclipse phenomenon is considered a beautiful and extraordinary phenomenon and interesting to observe using astronomical tools. From a scientific perspective, eclipses occur because the positions of the sun, moon, and earth are in a straigh line natural phenomenon occur naturally and can be scientifically From the perspective of astronomy, in the historical study of solar eclipses, it occurred at the time of the Prophet Muhammad. through the hadith clearly states that eclipses do not result in the death or birth of a person.Keywords: Eclipses, Science Perspective, and Astrology.